Interfacial Properties and Structure of Emulsions and Foams Co-Stabilized by Span Emulsifiers of Varying Carbon Chain Lengths and Egg Yolk Granules - Wenyan Liu; Jingxia Cao; Qixin Zhang; Weiqin Wang; Yuanping Ye; Senwang Zhang; Leiyan Wu (Foods)
Interfacial properties significantly influence emulsifying and foaming stability. We here explore the interfacial behavior of egg yolk granules (EYGs) combined with various Span emulsifiers (Span 20, 40, 60, 80) to assess their solution properties, interface dynamics, and effects on emulsifying and foaming stability. The results unveiled that as the Span concentration increased, particle size decreased from 7028 to 1200 nm, absolute zeta potential increased from 4.86 to 9.26 mv, and the structure became increasingly loosened. This loose structure of EYGs-Span complexes resulted in reduced interfacial tension (γ), higher adsorption rate (Kd), and improved interfacial composite modulus (E) compared with native EYGs. These effects were more pronounced with shorter hydrophobic chain Spans but diminished with longer chain lengths. Enhanced interfacial properties contributed to better emulsification and foaming stability, with EYGs-Span complexes displaying increased emulsifying ability and stability compared with natural EYGs. Emulsifying and foaming stability improved in the order of Span 20 > Span 40 > Span 60 > Span 80 as the Span concentration increased. The correlation analysis (p > 0.05) indicated that emulsifying stability was positively associated with interfacial composite modulus and negatively correlated with particle size. Consequently, EYGs-Span composites demonstrate considerable potential for use as effective emulsifiers in food industry applications.